Processing of human beta-globin mRNA precursor to mRNA is defective in three patients with beta+-thalassemia. - Maquat, L E (Proc Natl Acad Sci U S A, 1980)
Nucleated bone marrow cells from normal individuals and from three patients with homozygous beta+-thalassemia were pulse-labeled with tritiated nucleosides. The processing of the newly synthesized globin mRNA precursors was monitored by inhibiting additional transcription with actinomycin D for 30 min. Human beta-globin mRNA is derived from its precursor via a series of reactions that generate processing intermediates. In nonthalassemic cells the precursor is processed efficiently to mature mRNA during the chase. In contrast, in beta+-thalassemic cells the processing of beta-globin RNA is defective. In one patient the beta-globin mRNA precursor turns over during the chase, but some of the intermediate RNAs accumulate and are not processed to mRNA. In two other patients a large fraction of the precursor and intermediate RNAs is not processed to mRNA. The alpha-globin mRNA precursor and intermediates are processed efficiently to mRNA-sized molecules in thalassemic and normal cells. The reduction in the rate of beta-globin but not alpha-globin RNA processing accounts for the alpha/beta globin mRNA imbalance in thalassemic erythroid cells. We discuss the possibility that the genetic lesions in beta+-thalassemia are at splicing signal sites within intervening sequences of the beta-globin gene.